2014
DOI: 10.1074/jbc.m114.550525
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Threonine 34 in Mouse Podoplanin-Fc Reduces CLEC-2 Binding and Toxicity in Vivo While Retaining Anti-lymphangiogenic Activity

Abstract: Background: Podoplanin-Fc inhibits lymphangiogenesis, but also causes a bleeding disorder by binding to CLEC-2 expressed on platelets. Results: Mutation of threonine 34 in mouse Pdpn-Fc reduces 30-fold the binding to CLEC-2 and does not hamper its antilymphangiogenic activity. Conclusion: PdpnT34A-Fc is an active lymphangiogenesis inhibitor with a better tolerability. Significance: Mutagenesis of Pdpn-Fc is a valid approach to improve this tool for anti-lymphangiogenic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…These acidic residues interact with a series of Arg residues in CLEC-2. These data are consistent with the results of Bianchi et al (2014), which showed that in mouse podoplanin, O-glycosylation of Thr-34 (localized in PLAG1…”
supporting
confidence: 82%
“…These acidic residues interact with a series of Arg residues in CLEC-2. These data are consistent with the results of Bianchi et al (2014), which showed that in mouse podoplanin, O-glycosylation of Thr-34 (localized in PLAG1…”
supporting
confidence: 82%
“…20 In addition, blocking of podoplanin function by administration of podoplanin-Fc during late embryonic development resulted in a less complex diaphragmatic lymphatic network in pups. 41 Thus, it is likely that, early in development, podoplanin functionally contributes not only to the separation of the blood vascular and the lymphatic system but also to LV patterning. However, our data indicate that after birth, podoplanin is dispensable for proper LV maintenance and drainage function.…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic overexpression of soluble PDPN-Fc in mouse skin provoked platelet activation via CLEC-2, causing disseminated intravascular coagulation and thrombocytopenia [121]. This event required O -glycosylated T34, as mutation of this residue, considered to be essential for the binding of podoplanin to CLEC-2, reduced platelet activation and its side effects [122]. However, the mutant soluble PDPN-Fc retained the ability to inhibit lymphangiogenesis in vitro and in vivo [122], suggesting that the function of podoplanin in LECs is independent of binding to CLEC-2.…”
Section: Podoplanin In Inflammatory Lymphangiogenesismentioning
confidence: 99%
“…This event required O -glycosylated T34, as mutation of this residue, considered to be essential for the binding of podoplanin to CLEC-2, reduced platelet activation and its side effects [122]. However, the mutant soluble PDPN-Fc retained the ability to inhibit lymphangiogenesis in vitro and in vivo [122], suggesting that the function of podoplanin in LECs is independent of binding to CLEC-2. The above conclusion is contradictory with earlier reports showing that platelets inhibit lymphangiogenesis [58,123].…”
Section: Podoplanin In Inflammatory Lymphangiogenesismentioning
confidence: 99%